Man and his Homeland. The conception of man in L. Leonov’s works - Kuzmenko, S. (Literatūra, 1971)
One of the main aspects of the conception of man in Leonov’s works is the idea of man’s genetic blood bond with the world that produced him. According to this, of particular importance is the complex exchange of the relations constantly going on between the personality and the surroundings that formed him, between man and the earth that produced him. The relations of the hero and his homeland, symbolizing their genetic, natural, unbreakable links, become a peculiar means of typization in Leonov’s works. Man’s primary character is based on these relations as well as some other features, on the one hand characterizing it, on the other hand arising out of it. While proving the strength of man that arises out of his homeland and the depths of their conceptions, Leonov treats the relation between the hero and his homeland as the criterium of man’s inner value and at the same time as a means for man’s character formation.